2019
DOI: 10.1103/physrevlett.123.217002
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Two-Dimensional Fermi Surfaces and Unitary Spin-Triplet Pairing in the Heavy Fermion Superconductor UTe2

Abstract: We report first-principles and strongly-correlated calculations of the newly-discovered heavy fermion superconductor UTe2. Our analyses reveal three key aspects of its magnetic, electronic, and superconducting properties, that include: (1) a two-leg ladder-type structure with strong magnetic frustrations, which might explain the absence of long-range orders and the observed magnetic and transport anisotropy; (2) quasi-two-dimensional Fermi surfaces composed of two separate electron and hole cylinders with simi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 59 publications
6
42
0
1
Order By: Relevance
“…and this helps explain the high observed value of H c2 in UTe 2 , as we show below. The key point is the quasi-two-dimensional nature of the Fermi surface sheets parallel to the c-axis, established by ARPES 21 and ab initio calculations 17,22 , which can be approximated by writing the dispersion as…”
Section: Resultsmentioning
confidence: 99%
“…and this helps explain the high observed value of H c2 in UTe 2 , as we show below. The key point is the quasi-two-dimensional nature of the Fermi surface sheets parallel to the c-axis, established by ARPES 21 and ab initio calculations 17,22 , which can be approximated by writing the dispersion as…”
Section: Resultsmentioning
confidence: 99%
“…This may explain why UTe 2 does not undergo magnetic order in contrast to UCoGe and URhGe. A recent first-principles study proposes a similar scenario [41].…”
Section: Fssmentioning
confidence: 99%
“…The recent discovery of unconventional superconductivity (SC) in the uranium chalcogenide paramagnet UTe 2 with a superconducting transition temperature of T SC ∼ 1.6 K [1][2][3] opens new perspectives on superconducting topological properties including emergent Majorana quasiparticles at the verge of magnetic and electronic instability. Transport and thermodynamic measurements demonstrated that correlations play an important role in this system, requiring theoretical treatment beyond the local-density approximation approach [2,[4][5][6][7][8]. The closeness of UTe 2 to ferromagnetic quantum criticality [9] induces astonishing superconducting properties.…”
Section: Introductionmentioning
confidence: 99%